Energy Efficient Tree-Based Routing Algorithm for Wireless Sensor Networks - Ni Chen; Rong Wen (IEEE Access)
To address the issue of uneven sensor node distribution and unbalanced energy consumption leading to premature node death in wireless sensor networks, an energy efficient tree-based routing algorithm is proposed. The algorithm calculates the optimal number of branches that minimize network energy consumption by constructing a tree-based energy model. Based on the optimal number of branches, with the base station as the root node, a multi-layer tree routing is formed from near to far according to the distance between the node and the base station. During the formation of routing tree, the nodes whose residual energy of the nodes is less than the energy threshold can only become end nodes, thus avoiding premature death of the nodes due to excessive energy consumption of the nodes. Nodes transmit data to the base station along the routing tree. The routing tree is updated at dynamic intervals instead of every round to reduce energy consumption. Simulation results show that the algorithm has more balanced node energy consumption, lower network energy consumption, and longer network stability period and network lifespan than the other three protocols.